Angioplasty and Stenting for Carotid Artery Near-Occlusion - Shchehlov, Dmytro V.; Svyrydiuk, Oleh Ye.; Vyval, Mykola B.; Nosenko, Nataliia M.; Rzayeva, Farida H. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Carotid near-occlusion (CNO) is the type of severe atherosclerotic stenosis of the internal carotid artery (ICA) with or without collapse of the vessel distally to the narrow part. According to the North American Symptomatic Carotid Endarterectomy Trial (NASCET), severity of ICA stenosis highly correlates with the risk of stroke, except for cases of extremely critical stenosis > 94%, where the risk is lower, and, according to recent guidelines, conservative treatment is preferable. This consideration is questionable due to the recent data about early stroke recurrence and worldwide practice. Rapid improvement of endovascular technique during the last decade makes carotid angioplasty and stenting (CAS) a feasible option for the treatment of patients with CNO and is widely reported in the literature. However, in uncertain circumstances, more scientific data are necessary to fulfill the gap in indications, terms and risks of CAS for CNO. The aim. To evaluate the results of the treatment of patients with CNO after CAS. Materials and methods. Three hundred and fifteen patients were surgically treated at Scientific-Practical Center of Endovascular Neuroradiology of the National Academy of Medical Sciences of Ukraine due to ICA stenosis between 2010 and 2020. Among them, 39 (12.4%) patients (11 woman / 28 men (age 57.9±2.1 years) had CNO and underwent CAS at our Center. Patient population, clinical and radiological investigations, procedure compli-cations were investigated. Procedure complications (stroke, hemodynamic depression [HD] and hyperperfusion syndrome [HPS]) were meticulously studied. All the patients had routine ultrasound and clinical check 30 days after the procedure. Results. All the patients with CNO were successfully stented with the improvement of the site of stenosis after CAS, with only minimal residual stenosis in cases of severe HD. We observed two procedural vascular accidents, first patient had transient ischemic attack (TIA) and one had stroke due to middle cerebral artery occlusion after stent placement and further urgent mechanical thrombectomy. The patient had no neurologic decline and was discharged home. We didn’t observe any cases of myocardial infarction (MI) or death in our series during the hospital stay. HD was seen in 13 (33.3%) patients, and mostly resolved after the procedure except for 3 casesthat required prolonged intensive care unit stay. HPS was diagnosed in 2 (5.1%) patients and also didn’t have anyneurologic consequences after supportive care. During 30 days of follow-up, one (2.6%) patient had TIA because of anti-platelets cessation and 1 (2.6%) patient had MI after 1 week since discharge. All control images revealedstents patency without the evidence of critical residual stenosis. Conclusions. CNO remains important diagnostic and therapeutic challenge. Recent data showed high risk ofrecurrent stroke in case of CNO on best medical therapy, especially at an early stage, but it remains a preferred option according to guidelines. Considering worldwide improvement of stroke rates after CAS in patients with symptomatic ICA stenosis, further studies are warranted to evaluate its risk-benefit in case of CNO, especially with full collapse. Our data shows that CAS with careful preoperative diagnosis and planning is an effective procedure for selected patients with CNO.